Genotype and phenotype correlation in intracranial hemorrhage in neonatal factor VII deficiency among Thai children - Traivaree, Chanchai (Appl Clin Genet, 2017)
Congenital factor VII (FVII) deficiency is a rare inherited coagulopathy. The clinical manifestations and clinical findings vary widely, ranging from asymptomatic to life-threatening bleeding, including intracranial hemorrhage (ICH), with prolonged prothrombin time, normal partial thromboplastin time and normal platelet counts, which are confirmed by the low level of FVII assay. Treatment consists of fresh frozen plasma (FFP), prothrombin complex concentrates (PCCs), and recombinant activated FVII to treat bleeding and prophylactic therapy. Here, we report four patients with FVII levels <5% (severe type) who presented ICH during the neonatal period. The IVS6+1G>T was the most common (50%) mutation identified in our study, followed by the K376X nonsense mutation (37.5%). In our study, we found that genetic information affected the severity of congenital FVII deficiency with ICH.